Online learning perceptions, online learning challenges and online learning effectiveness during the pandemic covid-19 amongst teachers at primary cluster schools in Shah Alam, Selangor, Malaysia / Wardatul Hayani Wahab - Wahab, Wardatul Hayani (2023)
During the Covid-19 outbreak in Malaysia, schools were closed starting on 18 March 2020. Since that, teachers have had to go through online teaching, which requires the involvement of technology in teaching successfully. This study aimed to explore online learning perceptions, online learning challenges and online learning effectiveness during the pandemic Covid-19 amongst teachers at primary cluster schools in Shah Alam, Selangor, Malaysia. This study is guided by five research objectives and six research questions. Additionally, this study was conducted by descriptive correlational research design employing mixed methods as a research design. The population of the study consisted of teachers at primary cluster schools in Shah Alam, Selangor, Malaysia. 150 teachers from four cluster primary schools in Shah Alam were randomly selected and became the respondents of the current study. 30 non-sampled respondents from cluster primary school in Subang were used for the pilot study. A survey questionnaire was distributed to all respondents through Google Forms. The data for this study were analyzed through descriptive and inferential analysis including mean scores, standard deviation, Cronbach’s Alpha, Pearson’s Correlation Coefficient, and Regression using SPSS. The qualitative data were constructed in a form of open-ended questions to triangulate the quantitative data obtained. A 5-point Likert scale of online learning perceptions, online learning challenges and online learning effectiveness was used to rate the items in the questionnaire. Findings indicated that firstly, the level of online learning perceptions is at a low level (M = 1.93, SD = .454). Secondly, the level of online learning challenges is high (M = 4.10, SD = .164). Thirdly, the means score of online learning effectiveness is at a low level (M = 1.95, SD = .278) indicating that online learning is not effective during the pandemic Covid-19. Fourthly, the results from the correlation coefficient analysis indicated that there was a significant, positive and strong relationship (r = .827, p = .000) between online learning perceptions and online learning effectiveness during the pandemic Covid-19. Fifthly, the results from the correlation coefficient analysis indicated that there was not significant, negative and weak relationship (r = -.118, p = .151) between online learning challenges and online learning effectiveness during the pandemic Covid-19. Sixthly, the simple regression analysis revealed 68.4% (R2 = .684) of online learning effectiveness was contributed by online learning perceptions. Besides, there is no relative contribution between online learning challenges and online learning effectiveness during the pandemic Covid-19 amongst teachers at primary cluster schools in Shah Alam, Selangor, Malaysia. Furthermore, the qualitative findings tend to support the quantitative data obtained. Consequently, all these findings lead to some implications such as the extension of the corpus of knowledge, policy and training, and theoretical implications on the context of online learning perceptions and online learning effectiveness.